English in Singapore - Tan, Peter K W (International Journal of Language, Translation and Intercultural Communication, 2012)
This article discusses the various ways in which it is possible to theorise about the varieties of English in the world, in particular Kachru’s (1982) concentric circle model and Schneider’s (2007) phases of development in post-colonial varieties of English and I try to fi t Singapore English into these models, although in both cases there are some difficulties. I then provide the historical background to how English was spread to South-East Asia and note that English is moving towards first-language status. The key phonological, grammatical, lexical and discourse are outlined. I end by discussing some of the key elements to remember when considering non-Anglo Englishes like Singapore English.